You are on page 1of 2

# Engineering Mathematics 2

## End User Licensing Agreement

The contents are provided free of charge.
The materials provided for do not contain any warranty or otherwise implied.

REMARKS
ALL MATERIALS ARE PREPARED WITH MATHCAD; CERTAIN DIFFERENCES FROM WRITTEN FORM ARE
EXPECTED BUT CORRECT WITHIN THE MATHEMATICAL CONTEXT.

QA 2.1.A2(i)
Step 1 Given

dy
= 3⋅ x − 2
dx ;take integral on both side

⌠ ⌠
 dy  ⌠
3 ⋅ x − 2 dx dA
;property 
dx =
 dx 
⌡ dx = A
⌡  dx

y= 3 ⋅ x − 2 dx ;use formula #1

2
x
y = 3⋅ − 2⋅ x + K ;K is a constant
3

QA 2.1.A2(ii)

Step 1 Given

dy 2 1
= −
dx x 2 ;take integral on both side
x
⌠ ⌠
 dy  2 1 ⌠
− dA
;property 
 dx =  dx
dx x 2 dx = A
  x  dx
⌡ ⌡ ⌡

## ⌠ ;property (of integration)

y= 3 ⋅ x − 2 dx

⌡ ;use formula #1

3 2
y= ⋅ x − 2⋅ x + K
2 ;K is a constant

QA 2.1.A2(iii)

Step 1 Given

dy x+1
=
dx x ;take integral on both side

## 20091 em2 21_2.mcd Copyright 2008 1/2

Engineering Mathematics 2

⌠ ⌠
 dy  x+1
 dx =  dx ;reduce rhs integrand
dx x

⌡ 

 x 1
y= − dx
 x x

 1

1
 2 2 ;use formula #1
y= x −x dx

1 1
+1 − +1
2 2
x x
y= − +K
1 1
+1 − +1
2 2
3 1
2 2 2
y = ⋅ x − 2⋅ x + K ;K is a constant
3

QA 2.1.A2(iv)

Step 1 Given
Do you know that
g'( x) = 4x + 1 dg( x)
= g'( x) ?
⌠ ⌠ dx
 
 g'( x) dx =  4x + 1 dx ;use formula #1
⌡ ⌡

 x2 
g ( x) = 4   +x+K
2
2
g ( x) = 2 ⋅ x + x + K ;K is a constant

QA 2.1.A2(v)
Step 1 Given

## 2 Do you know that

g'( x) = 3 ⋅ x + 6⋅ x − 2 dg( x)
= g'( x) ?
⌠ ⌠ dx
  2
 g'( x) dx =  3 ⋅ x + 6 ⋅ x − 2 dx
⌡ ⌡ ;use formula #1

 x3+ 1   1+ 1 
g ( x) = 3   + 6⋅  x  − 2⋅ x + K
3 + 1  1 + 1

 x4   2
g ( x) = 3   + 6⋅  x  − 2⋅ x + K
4 2

3 4 2
g ( x) = x + 3⋅ x − 2⋅ x + K ;K is a constant
4